Water retention influences thigh skin temperature variation post-exercise: preliminary study of bioimpedance analysis and thermography data - Amato, Alessandra; Petrigna, Luca; Sortino, Martina; Amorim, Paulo Roberto S.; Musumeci, Giuseppe (Frontiers in Sports and Active Living, 2025)
ObjectivesThis study aimed to investigate the influence of body composition variables, focusing on the extracellular water level and gender difference, on infrared thermography detection during and post exercise.MethodOne hundred two participants were included in the study. Body composition was analyzed by bioimpedance, and three thermal imaging were taken before, at the end, and 5 min after a vigorous exercise. First, participants were divided by gender, and differences in skin temperature variation during exercise were highlighted. In the second analysis, the subjects were divided into three groups depending on the percentage of extracellular water. The correlation between body composition variables and skin temperature at the 3-time points was studied.Resultsan association between extracellular water (%) and basal thigh temperature both in the dominant leg (r: −0.27, p < 0.01) and non-dominant leg (r: −0.26, p < 0.01) was found; temperature variation analysis shows a significative temperature reduction between baseline and the end of exercise in both leg for (non-dominant: p < 0.001; dominant: p < 0.001) and a significative skin temperature increase after 5 min recovery, 0.14°C for the dominant leg (p > 0.05) and 0.12°C for the non-dominant leg (p > 0.05) considering the whole group. However, when we considered the separate group for extracellular contente the same significative decrease was found just in the lower water retention group (p < 0.05) and medium water retention group (p < 0.05). The high water retention group showed an opposite skin temperature trend in 5-min post-exercise recovery and had lower skin temperature at each time point compared with the other groups. The female group had lower skin temperature than the male at each time point.ConclusionWater retention could influence basal skin temperature and the temperature variation following vigorous exercise. A value of less than 45% of extracellular water should be considered for reliable use of thermal imaging. Further studies are needed to confirm this value.